2009
DOI: 10.1128/iai.00648-09
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Enables the Antimicrobial Activity of LL-37 in the Presence of Proteases of Porphyromonas gingivalis

Abstract: Proteolysis is a common microbial virulence mechanism that enables the destruction of host tissue and evasion from host defense mechanisms. Antimicrobial peptides, also known as host defense peptides, are effector molecules of the innate immunity that demonstrate a broad range of antimicrobial and immunoregulatory activities. Deficiency of the human LL-37 antimicrobial peptide was previously correlated with severe periodontal disease. Porphyromonas gingivalis, the major pathogen associated with periodontitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 51 publications
(46 reference statements)
2
59
0
1
Order By: Relevance
“…Saliva was previously shown to protect LL-37 from degradation by Porphyromonas gingivalis (33). As can be seen in Fig.…”
Section: Figsupporting
confidence: 59%
See 2 more Smart Citations
“…Saliva was previously shown to protect LL-37 from degradation by Porphyromonas gingivalis (33). As can be seen in Fig.…”
Section: Figsupporting
confidence: 59%
“…MSP, fibrinogen, and bovine serum albumin were attached to nitrocellulose membranes and were incubated with LL-37. The binding of LL-37 to the proteins was immunodetected using rabbit anti-LL-37 antibodies (33). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of hCAP-18 and LL-37 are increased in the GCF from chronic periodontitis patients (23). LL-37 is capable of proteolytically degradating by proteinases produced by P. gingivalis; however, the antimicrobial activity of LL-37 is still active in the existence of the proteinases in saliva (9). The susceptibility to periodontal diseases is increased in patients with morbus Kostmann disease, which causes neutropenia (24), Haim-Munk syndrome, and Papillon-Lefèvre syndrome which cause the dysfunction of neutrophil protease cathepsin C (10).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that P. gingivalis-induced CAMP (LL-37 gene) mRNA expression was up-regulated in IL-33 siRNA-transfected Ca9-22 cells. LL-37 is capable of proteolytically degradation by gingipains secreted by P. gingivalis; however, the antibacterial activity of LL-37 is still intact in the presence of P. gingivalis proteases [34]. In this study, we revealed that P. gingivalis induced IL-33 via PAR-2-PLC-p38/ NF-κB signaling pathways and that the IL-33 down-regulated LL-37 expression in human gingival epithelial cells.…”
Section: Future Prospects: Possible Roles Of Il-33 In Gingival Epithementioning
confidence: 60%